2003
DOI: 10.1177/1356336x03009001182
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education and Health: a Polemic or ëLet Them Eat Cake!í

Abstract: In recent years, teachers in the UK and elsewhere have been encouraged to include 'health aims' as part of the physical education curriculum. The widely reported worldwide 'rising tide of obesity' has been a major motivating concern. This article looks critically at 'obesity research', offers a way of reading it and suggests that many of its claims are at best over-exaggerated, at worst unfounded and, ironically, if translated uncritically in schools could damage the educational interests and health of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 8 publications
1
82
0
Order By: Relevance
“…Evans, 2003;Gard, 2004b;Gard & Wright, 2005;Kirk, 2006;Evans, 2007;Evans, Rich & Davies;Wright & Dean, 2007;Evans et al, 2008;Evans & Rich, 2011). Given the breadth of this paper it is not possible to explore these concerns in detail here, and indeed they are documented fully elsewhere, but they are clearly important to recognise and to briefly summarise.…”
Section: The Role Of Schools and Physical Education In Addressing Obementioning
confidence: 99%
See 2 more Smart Citations
“…Evans, 2003;Gard, 2004b;Gard & Wright, 2005;Kirk, 2006;Evans, 2007;Evans, Rich & Davies;Wright & Dean, 2007;Evans et al, 2008;Evans & Rich, 2011). Given the breadth of this paper it is not possible to explore these concerns in detail here, and indeed they are documented fully elsewhere, but they are clearly important to recognise and to briefly summarise.…”
Section: The Role Of Schools and Physical Education In Addressing Obementioning
confidence: 99%
“…A number of researchers (e.g. Evans, 2003;Evans, Rich & Davies, 2004;Gard, 2004a;Campos et al, 2006;Marsh, 2006;Evans et al, 2008;Evans & Rich, 2011) have questioned or refuted reported obesity figures and predictions, claiming that they are exaggerated, sensationalized, misreported and even meaningless and shallow. For example, based on an analysis of data for the period 1995 to , Marsh (2006 reported no statistically significant increase in average BMI for boys aged 5-15 and a generally similar picture for girls.…”
Section: The Scale Of the Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as will be revealed, these 'facts' are routinely issued with authority and conviction despite there being very few, if any, certainties to be found in the primary research on obesity (see Gard and Wright, 2001). Indeed, the relationships between obesity and health are far more tenuous, complex and contradictory than the 'obesity epidemic' discourse would have us believe (see, Evans, 2003;Gard and Wright, 2001;Flegal, 1999). There is a great deal we do not know about obesity, weight and its effect on health (see European Youth Heart Study Symposium, 2005).…”
Section: Scientifically Uncertainmentioning
confidence: 99%
“…The central concern here is the placing of moral responsibility on the individual to have a good diet and make certain 'lifestyle' choices around physical activity. By designating certain behaviours (around food and exercise) as either 'good', 'bad' or 'risky', obesity discourse is instrumental in manufacturing a public 'health scare' (see Evans, 2003;Gard and Wright, 2001). It creates a 'moral panic' about the state of an individual's or a nation's health and the choices they are to make to rectify it.…”
Section: Morality and The Bodymentioning
confidence: 99%